MulitaMiner: An LLM-Based Tool for Structuring Vulnerability Scanner Report - Lautert, Douglas; Machado, Beatriz; Kapelinski, Cristhian; Kreutz, Diego (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg_estendido.2026.33714, 2026)
Vulnerability scanners produce heterogeneous, vendor-specific PDF reports that hinder automated analysis and vulnerability management. We present MulitaMiner, an open-source tool that uses LLMs to extract structured records from these reports into a canonical 18-field schema via a segment-prompt-validate pipeline. Evaluated on 129 OpenVAS reports (6,343 findings) across three pipeline versions and five LLMs, MulitaMiner raises aggregate correctness from 67.5% to 78.3% and cuts omission from 14.1% to 2.8%; DeepSeek offers the best balance, tying for the lowest omission (2.7%) and posting the lowest hallucination (4.1%). MulitaMiner turns archived scanner PDFs into queryable data for CSIRT triage, prioritization, and tracking.